Variation in performance traits of laying hens and the relationships with egg quality and egg safety - Anene, Doreen Onyinye (2023)
The feed consumption, body weight, egg weight, and rate of lay of the hen, as well as the albumen, yolk, and shell characteristics of the egg, are important measures of productivity, quality, and safety in the layer industry. However, in the literature, there is little information on the onset and extent of variation of these traits among individual hens, the persistence of these differences during the laying period and how these variations are related to egg quality and safety as well as hen health and welfare. The overarching goal of this thesis was to control environmental variables such as food and housing conditions and determine the variation in hen performance, egg quality and organ characteristics between individual birds. This research also aimed to explore the effect of varying feed efficiency on hen body weight, egg production, egg quality, egg safety and organ characteristics from early lay to late laying stages. Finally, this research evaluated a dietary intervention to improve uniformity of hen and egg traits. To achieve these objectives, the first study investigated the inherent variation and associations in hen performance traits (feed intake, egg production, and body weight changes) and egg quality measurements (albumen, yolk, and shell characteristics) of individually housed hens in the early stages of lay. The second study in this thesis evaluated the effect of varying feed efficiencies on body weight changes, egg production, nutrient digestibility, and egg quality characteristics of individual ISA Brown hens in the mid laying stage of lay. The third study sought to estimate the effect of varying feed efficiency and body weight on organ characteristics and incidences of FLHS in mid laying hens. The fourth study examined the differences in the bacteriostatic activity and proteome composition of egg albumen from ISA Brown hens of varying FE while the final study evaluated the effect of temporary or permanent quantitative feed restriction beginning from point of lay, on performance traits, egg quality indices, organ characteristics and occurrences of fatty liver haemorrhagic syndrome of individually housed hens. Summarily, a total of 455 pullets were individually housed and monitored for performance and egg quality differences from 25 to 30 weeks of age. At 30 weeks old, the hens were ranked based on feed efficiency into high feed efficiency (HFE), medium feed efficiency (MFE) and low feed efficiency (LFE) groups, and then monitored for performance, egg quality and organ characteristics until the late stages of lay. The results from this research showed that important variations in hen and egg traits exists and these variations are present from the initial stages of lay. Hens maintained the feed efficiency ranking which they attained in early lay until at least 75 weeks of age. The HFE hen cohort consumed lesser feed and had a lower bodyweight compared to the hens from the LFE and MFE group. Interestingly, FE ranking did not have an effect on egg production up to 75 weeks. Hens ranked as LFE had higher abdominal fat weight, fatty livers, and higher fatty liver haemorrhagic syndrome (FLHS) lesion scores, compared to hens ranked as HFE. Eggs collected from hens ranked as HFE had a higher albumen quality and a stronger bacteriostatic activity against gram-negative Salmonella typhimurium and gram-positive Staphylococcus aureus, compared to the LFE groups. Proteomics profiling detected an additional 20 protein groups in albumen from HFE hens which were not found in albumen from LFE hens. There were no differences in the shell characteristics of eggs across all FE groups from 30 weeks up to 75 weeks. A quantitative feed restriction intervention study to improve uniformity of performance traits and egg quality was conducted. A total of 150 hens, placed into three feeding treatments - ad libitum feeding (ALF, from 22 to 46 weeks), temporary restricted (TRF, restricted until 40 weeks and transitioned to ALF status) and permanently restricted (PRF, restricted from 22 to 46 weeks), (n = 50 per treatment), were monitored from 22 weeks to 46 weeks of age. Hens on the TRF treatment showed compensatory feeding and body weight change increase when transitioned to ALF status. Although restricting feed consumption until 40 weeks of age did not control further feed intake and body weight gain, hens on the PRF treatment maintained a more uniform body weight, had better albumen quality, and had a lower fatty liver haemorrhagic lesion score compared to hens on the ALF treatment. This research showed that among individually housed ISA Brown hens, variation exists in hen traits which set in from the early stages of lay. These differences are associated with albumen quality, egg abnormality, abdominal fat deposition and incidences of fatty liver haemorrhagic syndrome. The findings of this study recommends that hen body weight should be controlled to around the breed exception from early lay as this has lifelong effects on the performance and health of the bird.